Transfer of allergic airway responses with antigen-primed CD4+ but not CD8+ T cells in brown Norway rats. - Watanabe, A (1995)
Activated CD4+ helper T cells have been demonstrated in asthmatic airways and postulated to play a central role in eliciting allergic inflammation; direct evidence of their involvement seems to be lacking. We hypothesized that CD4+ T cells have the potential to induce allergic responses to antigen challenge, and tested this hypothesis in a model of allergic bronchoconstriction, the Brown Norway rat, using the approach of adoptive transfer. Animals were actively sensitized to either ovalbumin (OVA) or BSA and were used as donors of T cells. W3/25(CD4)+ or OX8(CD8)+ T cells were isolated from the cervical lymph nodes of sensitized donors and transferred to naive BN rats. 2 d after adoptive transfer recipient rats were challenged by OVA inhalation, and changes in lung resistance (RL), bronchoalveolar lavage (BAL) cells, and serum levels of antigen-specific IgE were studied. After OVA challenge recipients of OVA-primed W3/25+ T cells exhibited sustained increases in RL throughout the entire 8-h observation period and had significant bronchoalveolar lavage eosinophilia, which was detected by immunocytochemistry using an antimajor basic protein mAb. Recipients of BSA-primed W3/25+ T cells or OVA-primed OX8+ T cells failed to respond to inhaled OVA. OVA-specific immunoglobulin E was undetectable by ELISA or skin testing in any of the recipient rats after adoptive transfer. In conclusion, antigen-induced airway bronchoconstriction and eosinophilia were successfully transferred by antigen-specific W3/25+ T cells in Brown Norway rats. These responses were dependent on antigen-primed W3/25+ T cells and appeared to be independent of IgE-mediated mast cell activation. This study provides clear evidence for T cell mediated immune mechanisms in allergic airway responses in this experimental model.